Experiencias en la implementación de la Norma Internacional de Información Financiera No. 1 en el sector cooperativo en Colombia y México (2015)
This article outlines the changes and the impact that has been generated in Colombian cooperatives by the adoption of International Financial Reporting Standards IFRS, this due to the importance of standards today, about 130 countries are presented financial information under this model, due to the need to standardize financial information, to facilitate analysis and promote foreign investment, since the data obtained with this standard are real and comparable to the global market. For Colombia is important to know the convergence process conducted in other Latin American countries, that is why we inquire about the adoption process undertaken by Mexico in recent years